2021
DOI: 10.1016/j.breast.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Metastasectomy versus radiation of secondary sites in stage IV breast cancer: Analysis from a national cancer registry

Abstract: Locoregional therapy at primary or secondary sites in breast cancer may be associated with improved survival as compared to systemic therapy alone. We explored the sociodemographic and clinicopathologic factors associated with the use of radiation versus surgical resection of metastatic sites (metastasectomy) in patients with de novo stage IV breast cancer, followed by the associated overall survival. Methods: We sampled the National Cancer Database for patients with de novo stage IV breast cancer, (2010e2017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Koizumi et al 52 also demonstrated similar increase in survival for those with one metastatic foci, but had a higher rate of patients with solitary bone metastasis at 41%. A recent review of the United States National Cancer Database of over 22 000 patients with de novo stage IV breast cancer found that metastasectomy was associated with improved survival when compared to those treated with radiation and the bone‐metastasis‐only cohort was 31.6% of the study population 53 …”
Section: Disease Specific Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koizumi et al 52 also demonstrated similar increase in survival for those with one metastatic foci, but had a higher rate of patients with solitary bone metastasis at 41%. A recent review of the United States National Cancer Database of over 22 000 patients with de novo stage IV breast cancer found that metastasectomy was associated with improved survival when compared to those treated with radiation and the bone‐metastasis‐only cohort was 31.6% of the study population 53 …”
Section: Disease Specific Considerationsmentioning
confidence: 99%
“…A recent review of the United States National Cancer Database of over 22 000 patients with de novo stage IV breast cancer found that metastasectomy was associated with improved survival when compared to those treated with radiation and the bone-metastasisonly cohort was 31.6% of the study population. 53 In a retrospective review of 115 individuals with metastatic breast cancer to bone, Wegemer et al 55 found that patients with solitary lesions treated with wide resection had an improved survival rate. In contradistinction, Durr et al 56 found that wide resection in patients with solitary bone metastasis did not significantly improve survival, although the number of patients who received this treatment was limited (6 of 70).…”
Section: Breast Cancermentioning
confidence: 99%
“…13 In general, the orthopedic oncology community has placed greater consideration on the benefits of en bloc resection and EPR for appendicular MBD in the appropriate clinical scenario. [13][14][15][16] Using a large retrospective dataset, we asked (1)…”
Section: Introductionmentioning
confidence: 99%
“…While survival in patients with MBD requiring orthopedic surgery has shown unclear temporal trends, 12 a recent study of femoral metastasis secondary to renal and lung carcinoma demonstrated measurable impact of biologic anti‐neoplastic agents on patient survival 13 . In general, the orthopedic oncology community has placed greater consideration on the benefits of en bloc resection and EPR for appendicular MBD in the appropriate clinical scenario 13–16 …”
Section: Introductionmentioning
confidence: 99%